Intractable hypoglycemia in an elderly lady with breast cancer - Khalid Farooqui; Hassan Abuzaid; Riyadh Hamammy; Mohammed Milad (Wolters Kluwer Medknow Publications, 2018)
Paraneoplastic hypoglycemia is one of the rare causes of noninsulin-mediated hypoglycemia, which has been encountered mostly with solid tumors or mesenchymal in origin; however, it can also occur in patients with diverse kinds of tumor origin. Hypoglycemia related to tumors can be induced by different hormones produced by different tumors - for example, excessive secretion of insulin by islet cell tumors (insulinoma and neuroendocrine tumors); insulin-like growth factor 2 (IGF2) from mesenchymal and epithelial tumors; and rarely by secretion of IGF1, cytokines, and catecholamines or increased tumor metabolism of glucose. Herein, we report the case of an 89-year-old female, known to have type 2 diabetes mellitus with frequent hospital admission due to recurrent episodes of severe hypoglycemia, which was initially attributed to the insulin therapy she was taking; the patient continued to have episodes of hypoglycemia even after cessation of insulin. During her previous admission, she was found to have a swelling over the left breast. Ultrasound-guided biopsy was done and histopathology was suggestive of an invasive ductal cell breast carcinoma. We eventually found that these episodes of severe hypoglycemia were secondary to the paraneoplastic effect of invasive ductal cell carcinoma of the breast.